Correlation between Neutrophil/Lymphocyte Ratio (NLR), lipid profile, lesion location and vascular cognitive impairment in acute ischemic stroke patients - Ira Ristinawati; Kenneth Tan; Benedictus Benedictus; Muhammad Hafizhan; Stefanus Erdana Putra; Suroto Suroto; Diah Kurnia Mirawati; Subandi Subandi; Rivan Danuaji; Pepi Budianto; Yetty Hambarsari; Baarid Luqman Hamidi; Hanindia Riani Prabaningtyas; Ervina Arta Jayanti Hutabarat; Teddy Tejomukti; Raden Andi Ario Tedjo (Faculty of Nursing Universitas Padjadjaran, 2024)
Background: Stroke is the leading cause of long-term disability with significant clinical and socioeconomic impact worldwide. Hyperlipidemia and inflammation play major roles in ischemic stroke. This research focuses on the correlation of three factors, namely Neutrophil-Lymphocyte Ratio (NLR), lipid profile, and lesion location, with Vascular Cognitive Impairment (VCI). These factors may serve as potential predictors for VCI. Purpose: This research aims to study the correlation between NLR, lipid profile, and lesion location with vascular cognitive impairment. Besides, this research aims to explore those potential biomarkers as predictors of vascular cognitive impairment. Methods: This was a cross-sectional study which included 107 patients diagnosed with ischemic stroke from February 2022 to January 2023 with a history of admission to the hospital within 72 hours. After signed an informed consent form, every patient had history taking, physical exam, lipid profile, routine blood test, Mini Mental State Examination (MMSE) and Montreal Cognitive Assessment Indonesian Version (MoCA-Ina) on the first hospital day. Statistical tests were done with Spearman correlation method. Results: The data distribution was not normal for INR and MoCA-INA values (p<0.05). Total cholesterol was insignificantly (p=0.092) correlated with MoCA-INA score with low correlation value (r=-0.293). HDL was significantly (p=0.035) correlated with MoCA-INA score with moderate correlation value (r=0.461). LDL was significantly (p=0.028) correlated with MoCA-INA score with low correlation value (r=-0.387). Triglycerides was insignificantly (p=0.440) correlated with MoCA-INA score with very weak correlation value (r=-0.137). NLR was significantly (p=0.015) correlated with MoCA-INA score with moderate correlation value (r=-0.412). Conclusions: Lipid profile is correlated with cognitive impairment in post stroke patients, with HDL being a protective factor, and LDL as risk factor. NLR was associated with worse cognitive function and LDL was directly proportional to NLR. Lesion location reporting was highly heterogeneous and more uniformed reporting is recommended for future research.